SELECTIVE HYDROGENATION OF BENZENE OVER RH-PROMOTED ZEOLITE CATALYSTS (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Studied selective hydrogenation process of benzene over Rh- promoted zeolite catalysts. Developed methods of application modifying by active ingredients. Determine the effect of the rhodium content in the hydrogenation of benzene. By gas-liquid chromatography, the reaction products of various catalysts. The structure and morphology of synthesized modified carbon materials by electron microscopy.